Optimasi Parameter Pemotongan Mesin Bubut CNC Terhadap Kekasaran Permukaan dengan Geometri Pahat yang Dilengkapi Chip Breaker - Wibolo, Achmad; Wahyudi, Slamet; Sugiarto, Sugiarto (Rekayasa Mesin, 2011)
In machining operation, the quality of surface finish is an important requirement for many turned workpieces. Thus, the choice of optimized cutting parameters is very important for controlling the requied surface quality The focus of present experimental study is to optimize for cutting speed, feed rate, and radius chip breaker using two performance measures, metal removal rate and surface roughness. Response Surface Methodology (RSM). has been applied for developing models in the form of multiple regression equations correlating dependent parameters with cutting parameters and radius chip breaker, in a turning process. The central composite rotatable design was used to plan the experiment, and analysis of variance were employed to study the performance characteristics for three variable independent in turning operation. A second-order model which can describe the relation then to find combination between cutting parameters and radius chip breaker which resulting the maximum metal removal rate and minimum surface roughness. The experimental results reveal that the most significant cutting parameters for surface roughness is cutting speed, followed by feed rate and radius chip breaker. Based on the optimization results, recommended cutting speed, feed rate, and radius chip breaker is 35 m/mt, 0,2819 mm/rev, and 0,85 mm. By implementing this parameters, the surface roughness and metal removal rate is 2,18 Î¼m and 6230,80 mm3/mt.Keywords : Surface Roughness, Metal removal rate, response surface methodology, turning